Essays on health care: New insights into the economic burden of population ageing and the implementation of health policies aimed at promoting evidence-based clinical practice and consistency in the delivery of hospital care - Anna Kollerup Iversen (University of Copenhagen, Department of Economics, 2022)
This thesis consists of three self-contained chapters. Each chapter casts light on different aspects of the challenges that national health authorities face in providing universal health care coverage under resource constraints and under the continual introduction of new knowledge and new expensive medical advances. To inform the debate on the future economic burden of population ageing and possible threats to the sustainability of universal health care coverage, the first chapter examines static and dynamic properties of the past decade's health care expenditure patterns across age, disease groups and time in Denmark. The second and third chapters examine the implementation of two evidence-based health policies, namely the implementation of national clinical practice guidelines and a regulation of the supply of hospital care by centralization to fewer and larger clinical facilities. The policies had the common goal of promoting evidencebased clinical practice and procedures in hospital care by mitigating slow adoption of new knowledge and reducing variation in the adoption of new medical advances, routines and procedures. The second chapter analyzes the effects of centralizing breast cancer care to fewer high-volume clinics on both cost-saving metrics and the quality of care that closure-affected patients receive. The third chapter explores whether consistency in the delivery of health care is achieved when introducing a new treatment with both national clinical guidelines and care centralization.
Keywords: 330